Perancangan Sistem Penjualan Material Bangunan Pada Ud. Mulya Sentosa Bebasis Web E-Commerce - Betesda Sinaga; Jehan Saptia Kurmia (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
The rapid development of information and communication technology at that time has spawned new innovation breakthroughs that are very beneficial to the community, including e-commerce. At present, only by accessing e-commerce through the Internet, we can view the goods we want, find out the details of the goods and transact with each one without being limited by time and distance. U.D Mulya Sentosa is one of the manufacturers engaged in the sale of building materials. The sales system at UD.Mulya Sentosa is still in the traditional way, where consumers have to go directly to the store to make purchases and know the product availability and the type of advertising only using word of mouth through the media, resulting in a limited sale and distribution of buildings on a large scale and reporting limitations. Based on the above problems, UD Mulya Sentosa developed a building material sales system based on web e-commerce. In creating this web e-commerce using the waterfall method, using the PHP programming language, the MySQL database and using the Visual Studio Code tool. The purpose of creating a web e-commerce based sales system is to provide promotional media for businesses so that sales marketing becomes broader and sales report management becomes more convenient.